Causas de infecciones asociadas a la atención de salud en la unidad de cuidados críticos - Pandi Barrionuevo, Yomaira Alexandra (2025)
Healthcare-associated infections are considered errors in healthcare, most of which are preventable. They also represent an indicator of health care quality and patient safety. The article was conducted with the aim of identifying the causes that contribute to the occurrence of healthcare associated infections in the Critical Care Unit, through a comprehensive review of the scientific literature and analysis of relevant data. The study was developed according to the qualitative, non-experimental, documentary approach, which consisted of a literature review according to the Preferred Reporting Items for Systematic reviews and Meta- Analyses (PRISMA) method, which allowed the identification of 341 studies. Fifteen studies were included in the review for critical analysis. The results indicate that the risk of contracting one of these infections varies according to the complexity of the service or intervention provided, its location within the health care center, the high complexity of the care received, the clinical condition and individual features of each patient, the procedures or interventions required, the pathogenic microorganism responsible and its pattern of sensitivity and resistance to antibiotics. In the literature consulted, the main factor that is reported as a cause of infection associated with health care in the Critical Care Unit is symbolized by invasive procedures (catheters, probes, invasive mechanical ventilation and tracheostomy). Such information is relevant to carry out the required epidemiological surveillance.